The Politics of Biblical Interpretation: A ‘Criticism of Criticism’ - Morrow, Jeffrey L. (New blackfriars, 2010)
Following Joseph Ratzinger's call for a ‘criticism of criticism’, this article situates the history of modern biblical criticism in its political context within the centuries long church state conflict. Beginning with Medieval Muslim polemical literature, this article traces through history the politically and theologically motivated philological analyses and hostility toward spiritual exegesis which formed the foundation upon which eighteenth and nineteenth century biblical criticism built. Rather than the result of some objective scientific enterprise, the methods modern Bible scholars employed often served state politics as well as other prior commitments.